Hierarchical and distributed control concept for distribution network congestion management. Issue 3 (1st February 2017) - Kulmala, Anna; Alonso, Monica; Repo, Sami; Amaris, Hortensia; Moreno, Angeles; Mehmedalic, Jasmin; Al‐Jassim, Zaid
Abstract : Congestion management is one of the core enablers of smart distribution systems where distributed energy resources are utilised in network control to enable cost‐effective network interconnection of distributed generation (DG) and better utilisation of network assets. The primary aim of congestion management is to prevent voltage violations and network overloading. Congestion management algorithms can also be used to optimise the network state. This study proposes a hierarchical and distributed congestion management concept for future distribution networks having large‐scale DG and other controllable resources in MV and LV networks. The control concept aims at operating the network at minimum costs while retaining an acceptable network state. The hierarchy consists of three levels: primary controllers operate based on local measurements, secondary control optimises the set points of the primary controllers in real‐time and tertiary control utilises load and production forecasts as its inputs and realises network reconfiguration algorithm and connection to the market. Primary controllers are located at the connection point of the controllable resource, secondary controllers at primary and secondary substations and tertiary control at the control centre. Hence, the control is spatially distributed and operates in different time frames.